تحديد معامل مرونة المادة عن طريق قياس العيوب الناتجة عن انعطاف الجائز المحمل بحمولات الانحناء - Asmar, Haitham (Latakia University Journal -Engineering Sciences Series, 2019)
تحديد معامل مرونة المادة عن طريق قياس العيوب الناتجة عن انعطاف الجائز المحمل بحمولات الانحناء هيثم أسمر يقدم هذا البحث نموذجًا نظريًا وحلاً تصميميا للجهاز الذي يحدد معامل المرونة عن طريق ثني المادة (عينات الاختبار) بدلاً من التمدد المعتاد. تم تصميم الجهاز وتجميعه واختباره بنجاح في المختبر. تم إجراء تحديد تجريبي لمعامل المرونة عن طريق قياس انحراف العينات تحت الحمل الثابت بالاضافة لحساب معامل المرونة من العلاقات النظرية بالإضافة الى إجراء القياس على الجهاز و تحليل أخطاء القياس الناتجة عن الجهاز.بالنتيجة تبين أن أخطاء القياس بحدود %2,لذلك يمكن اعتبار أن قيمة معامل المرونة المقاسة على الجهاز المصمم تظل كافية للقيمة النظرية لمعامل المرونة للمواد التي تم تحليلها. The paper presents a theoretical model and design solution for the device which determines the modulus of elasticity by bending the material (test samples), instead of the usual stretching. The device was designed, assembled and successfully tested in the laboratory. Experimental determination of the elastic modulus was conducted by measuring the deflection of samples under a constant load. The elasticity factor was calculated from the theoretical relations as well as the measuring procedure on the instrument. The measurement errors of the instrument were analyzed. As a result, the measurement errors were found at 2%. Therefore, Values of the elastic modulus resulted from theoretical relations. Measurement was performed and measurement errors, i.e. device errors, were analyzed.